Crack spatial distributions and dynamic thermomechanical properties of 3D braided composites during thermal oxygen ageing. (May 2021) - Wu, Yuanyuan; Xun, Limeng; Huang, Shuwei; Ren, Chunlei; Sun, Baozhong; Gu, Bohong
Abstract: Thermal oxygen ageing behaviors of polymer matrix composites depend on resin and preform architecture. This paper concerns effects of braided architectures on thermo-oxidative ageing, including inner and surface crack initiations and propagations in 3D braided carbon fiber/epoxy composites. The ageing behaviors of unidirectional (UD) was also tested for comparison. Attenuated total reflectance Fourier transform infrared spectroscopy, two-dimensional infrared correlation spectrum, and micro-computer tomography technique have been used to characterize ageing behaviors. Aromatic formation was found ether on the surface of epoxy resin appeared prior to peroxide. The resin shrinkage could appear on the surface, and the changes of shrinkage rate of the UD composites and the 3D braided composites were consistent with cracks volume fraction. In addition, the cracks in the 3D braided composites initiated later and propagated slower than those in the UD composites. The 3D braided structure was beneficial for retaining the stiffness and damping properties after ageing.